A Robust Mn Catalyst for H2O2 Disproportionation in Aqueous Solution. Issue 22 (31st May 2013) - Lee, Wei‐Tsung; Xu, Song; Dickie, Diane A.; Smith, Jeremy M.
Abstract: The pyridinophane complex [Mn(Py2 N2 )(H2 O)2 ] 2+ catalyses the disproportionation of H2 O2 in aqueous solution over a wide pH range. Kinetic investigations reveal an induction period, which is proposed to involve the formation of a hydroperoxo intermediate, as well as evidence for catalyst self‐inhibition. A catalytic cycle involving mononuclear intermediates has been proposed. Spectroscopic investigations under turnover conditions are consistent with this proposal and show that the resting state of the catalyst is a mononuclear Mn II complex. The robustness of the catalyst is evidenced by its ability to achieve turnover numbers of 58000 in aqueous solution. Abstract : The macrocycle complex [(Py2 N2 )Mn(H2 O)2 ] 2+ catalyses H2 O2 disproportionation in aqueous solution, achieving large turnover numbers and operating over a wide pH range. Mechanistic studies implicate a monomeric catalyst for H2 O2 disproportionation.